Cavernous Sinus Syndrome: A Unique Presentation of CD5+ Diffuse Large B-Cell Lymphoma - Louis Arens; Iyerus Tariku (Annals of Internal Medicine: Clinical Cases)
Abstract/Background Cavernous sinus syndrome (CSS) is characterized by signs and symptoms that result from the compression and/or disruption of function of the dural venous sinus. Causes of CSS include tumors, inflammation, infection, trauma, and cavernous sinus thrombosis. Although neoplasm is one of the most common causes of CSS in a series of case analyses, CSS is an exceedingly rare initial presentation of lymphoma. Additionally, CSS is a potential cause of secondary headaches, particularly in elderly patients with concomitant neurologic deficits. Here, we discuss a patient case of de novo CD5+ diffuse large B-cell lymphoma that initially presented as CSS.